FAKTOR PEMILIHAN MODA PENGUNJUNG CAR-FREE DAY KOTA BANDUNG - Muhammad Abdul Mubdi Bindar (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
This paper aims to reveal the dimension underlying variables that affect the trip makers; mode choice to reach Car-Free Day location, taking Bandung as a case study. Twelve variables are gathered from several works of literature, namely trip cost, parking cost, trip duration, trip distance, number of people on the trip, the highest number of lanes in the trip, the age of the trip maker(s), number of vehicle ownership, whether those are motorized or non-motorized, and the number of household member. Correlations between variables are more than possible to find in that amount. Therefore, a principal component analysis is used to group the variables into factors, representing the structure or dimension laid down beneath them. This method shows that four groups of variables, or factors, are generated. The result then is compared to some literature that priorly have been reviewed. The first dimension is called “trip characteristics” which elements are trip duration, the highest number of lanes in the trip, and trip distance. The second dimension, namely “out-of-pocket cost”, is built upon in-vehicle trip cost and parking cost. The third dimension is a group of three vehicle ownership, i.e car, motorcycle, and bicycle ownership, hence the name “vehicle ownership” dimension. The fourth dimension is labeled “trip-maker characteristics”, with its variables being the number people involved in the trip and the age of the trip-maker.